Effects of herbal medicine on clinical characteristics and biological markers in pulmonary pure ground-glass nodules: study protocol for a multicenter randomized triple-blind controlled trial - Tan, Shi-Yan; Ma, Qiong; Wang, Qian; Wu, Tao-Yu; Wang, Zi-Fan; Mao, Zong-Yi; Xiao, Chong; Zheng, Chuan; You, Feng-Ming; Ren, Yi-Feng (Frontiers in Medicine, 2025)
BackgroundThe widespread use of chest computed tomography (CT) screening has led to more frequent detection of pure ground-glass nodules (pGGNs). A subset of pGGNs carries a potential risk of malignant transformation. However, the current management strategy for stable pGGNs predominantly involves surveillance, with a notable absence of effective intervention strategies. Traditional Chinese medicine (TCM), as an adjunctive therapy, offers considerable promise. Preclinical studies indicate that Chuanjie Granules (CJG), a TCM compound formulation, may have potential benefits in reducing the size of pGGNs. However, there is a lack of strong evidence from large-scale randomized controlled trials. Consequently, this study aims to evaluate the clinical effectiveness and safety of CJG for pGGNs through a well-designed clinical trial and explore its mechanisms of action.MethodsThis study is a prospective, randomized, triple-blind, placebo-controlled, multicenter clinical trial designed to enroll 172 patients who have been radiologically diagnosed with pGGNs. Participants will be randomly allocated in a 1:1 ratio to receive either CJG or placebo, both with standard health education. The intervention lasts 3 months with participants receiving either CJG or a placebo, followed by a 1-year observational period after treatment. The primary outcome is the change in pGGN maximum diameter, while secondary outcomes include nodule reduction rate, density changes, malignancy risk, and patient-reported outcomes. The study will also use 16S rRNA gene sequencing and gas chromatography–mass spectrometry-based metabolomics to examine oral and gut microbiota and explore microbial-metabolic mechanisms.DiscussionThis study aims to rigorously assess the efficacy and safety of CJG and explore its mechanism of action in the intervention of pGGNs through a randomized controlled trial. Positive outcomes are anticipated to furnish the first high-quality evidence-based medical support for the use of TCM in the early intervention of pGGNs, thereby potentially enhancing clinical decision-making processes.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025001413.